Parallel planning and the paediatric critical care patient. Issue 10 (31st January 2019) - Sidgwick, Peter; Fraser, James; Fortune, Peter-Marc; McCulloch, Renee
Abstract : A growing number of children with life-limiting conditions (LLCs) are being cared for in paediatric critical care (PCC) settings. Children with LLCs admitted to PCC are at a high risk of developing complications and many die after prolonged admissions. Relatively few of these patients and their parents or carers have had documented discussions about their wishes for care in the event of a serious clinical deterioration before admission to PCC. There is a need for improved understanding of (1) how parents arrive at decisions regarding what is best for their child at times of critical illness and (2) the role of parallel planning and advance care plans in that process. This review examines the complexities of decision-making in children with LLCs who are admitted to PCC settings.